Post a New Question


posted by .

Find the second derivative of the function.
f(x) = e−3x + 5e4x

  • Calc -

    f(x) = e^(−3x) + 5e^(4x)
    Note that the derivative of e^x is equal to e^x times the derivative of the exponent with variable x:
    d/dx (e^x) = e^x dx

    applying this,
    f'(x) = -3e^(-3x) + 20e^(4x) : First derivative

    f''(x) = 9e^(-3x) + 80e^(4x) : Second derivative

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question